Geochronology and Geochemistry of Late Cretaceous Plutonic Rocks in Southeastern Anatolian Orogenic Belt, Eastern Türkiye: Implications for Petrogenesis and Tectonic Evolution - Sar, Abdullah; Rizeli, Mustafa Eren (Mdpi, 2026)
Late Cretaceous plutonic rocks are commonly observed along the Southeastern Anatolian Orogenic Belt (SAOB), which constitutes a significant part of the Alpine-Himalayan Orogenic Belt. Here, we present new whole-rock geochemical analyses, zircon U-Pb ages, and zircon trace element data of plutonic rocks located in the SAOB (eastern T & uuml;rkiye). This study aims to determine the petrogenesis of the studied plutonic rocks in light of new data and to contribute to the tectonic evolution of the SAOB. Geochemical data demonstrate that the studied granodiorites, diorites, and gabbros are tholeiitic-calc-alkaline in composition, metaluminous, and I-type granite. Zircon U-Pb ages yielded crystallisation ages of 73.52 +/- 0.24 Ma for the studied granodiorites and 78.86 +/- 0.39 Ma for the diorites. These age data indicate that the studied plutonic rocks represent the youngest granodiorite and diorite formations observed around the study area. High Th/U ratios (granodiorite: 0.15-0.29; diorite: 0.31-0.96) and positive Ce/Ce* (granodiorite: 8.11 to 609.86; diorite: 58.07 to 564.31) and negative Eu/Eu* (granodiorite: 0.49 to 0.62; diorite: 0.59-0.97) values obtained in zircon grains suggest that they are of magmatic origin. Geochemical data indicate that the studied diorites and gabbros originate from a spinel-bearing source representing shallow depths. In light of all the data, the studied plutonic rocks are products of arc magmatism resulting from the subduction of the NeoTethys Oceanic lithosphere along the SAOB.
Keywords: petrogenesis; eastern T & uuml;rkiye; Southeastern Anatolian Orogenic Belt; zircon U-Pb data; zircon trace element